ORIENTALISMS IN MIKHAIL GAR'S NOVEL "THE DUST OF BABYLON" (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article examines the work of the Russian-speaking contemporary writer Mikhail Gar. His work "The Dust of Babylon" is analyzed. The novel "The Dust of Babylon" is imbued with love for his native land. Speaking about orientalism in the works of Russian-speaking authors, Mikhail Gar is the most prominent representative of his time, who pays special attention to national origins.